When dealing in and implementing Boolean Equations, we are forced to reduce

NAND and

NOR into regular

AND and

OR statements. To do this, we follow

Demorgan's Laws:

_____ _ _
A * B == A + B A NAND B == Not A OR Not B
_____ _ _
A + B == A * B A NOR B == Not A AND Not B
__-__---__-__
A * B == A + B A AND B == Not A NOR Not B
__-__---__-__
A + B == A * B A AND B == Not A NOR Not B

This, of course, expands to equations of several terms, such as

*A NOR B NOR C == Not A AND Not B AND Not C*.

**A simple example:**

-----__-----__
A * (B * C)
_ __-----__
A + (B * C)
_
A + (B * C) (the two negations cancel)

**Yet Another:**
__ - -__
(A + B) * (C + E)
_____ __- -__
(A + B) + (C + E)
_ _
(A * B) + (C * E)